Keefektifan Penggunaan Modul Biologi Molekuler Berbasis Learning Cycle 7E untuk Memberdayakan Kemampuan Berpikir Mahasiswa - Nugroho, Anwari Adi (Universitas Sebelas Maret, 2018)
This study aimed to know effectiveness of the use of molecular biology module based on learning cycle 7E to empower the thinking ability (cognitive) of biology education students. The study type was quasi experiment with one group pretest postes design, using one class that was experiment (implementation of module). The experimental class was treated with pretest and postes. Data obtained were data of students' thinking ability and data source obtained from biology student of Veteran Bangun Nusantara Sukoharjo University. The data was analyzed by inferential statistics. Measurement of students' thinking ability before and after the implementation of module was calculated with N-Gain. The data of thinking ability was also analyzed using t test paired sample, preceded by homogeneity and normality test. The result of this study showed that the improvement of thinking ability from pretest and posttest score after N-Gain tested, the students got N-Gain score 0.75-1 as many as 7 people with high category, N-Gain score 0.31-0,70 as many as 11 people was categorized moderate and N-Gain score from 0.07-0.10 as many as 4 people with low category.Â Pretest and postes score of students' thinking ability then tested of homogeneity and normality showed that the data was normall and homogeneous so that it continued with t paired sample test. T test Paired sample obtained Asymp value. Sig. (2-tailled) below 0.05 0.000, it can be concluded that there were significant differences between prestes and postes students' thinking ability. It shows that the use of molecular biology module based on learning cycle 7e effectively empower the thinking ability of biology students.